2014
DOI: 10.1155/2014/307403
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Highest HXR Yield in Plasma Focus Device Using Adaptive Neurofuzzy Inference System to Optimize Anode Configuration

Abstract: Adaptive neurofuzzy inference system (ANFIS) is investigated to optimize the configuration of anode shape in plasma focus devices to achieve the highest X-ray yield. Variables of discharge voltage, filling gas pressure, and angles of anode slopes (Φ1and Φ2) are chosen as input parameters, while the output is designated to be the radiated hard X-ray intensity. The trained ANFIS has achieved good agreement with the experimental results and has mean relative error percentages (MRE%) 1.12% and 2.18% for training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In this regard, the typical current oscillograms and I-V characteristic of the CPA, obtained for the two types of working gas, shown in figures 2(a) and (b). These discharge current oscillograms are in well agreement with the oscillograms presented in other studies [19,20] and represent a rapidly damping waveform. This indicates a low inductance of the system and demonstrates the fact of effective transfer of the energy stored in the capacitors.…”
Section: Resultssupporting
confidence: 90%
“…In this regard, the typical current oscillograms and I-V characteristic of the CPA, obtained for the two types of working gas, shown in figures 2(a) and (b). These discharge current oscillograms are in well agreement with the oscillograms presented in other studies [19,20] and represent a rapidly damping waveform. This indicates a low inductance of the system and demonstrates the fact of effective transfer of the energy stored in the capacitors.…”
Section: Resultssupporting
confidence: 90%
“…The optimization of plasma focus devices for these applications are necessary in terms of neutron yield or x-ray productions. Therefore, neutron optimization studies [25][26][27] and x-ray optimization studies [28][29][30][31] are conducted experimentally and theoretically with different gases.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that decreasing cylindrical anode length improves soft x-ray yield but using tapered anode did not improve soft x-ray yield in the device [30]. Static inductance, anode length, anode radius, and gas pressure are also investigated for neon soft x-ray yield optimization in plasma focus [31][32][33][34]. These studies show that there is an optimum gas pressure as well as an optimum static inductance when the optimum anode length and anode radius are used to increase soft x-ray yield in plasma focus.…”
Section: Introductionmentioning
confidence: 99%
“…The soft X-ray emission from dense plasma focus is according to two mechanisms: linear radiation and continuum radiation (recombination and Bremsstrahlung radiation) [18][19][20]. The hard X-rays are also produced by the collisions of electron beams resulting from the collapse of the plasma pinch with the anode [21][22][23].…”
Section: Introductionmentioning
confidence: 99%